Phytochemicals from food plant residues an approach to environmental clean-up. - Nagar, Shipra (My University, 2011)
Increased consumption of ‘ready to eat’ foods in modern lifestyle has resulted in several health problems. Natural health-protective and disease-preventive products are in great demand nowadays due to both consumers’ preference and health concerns. By-products of fruits and vegetables from commercialization and industrial transformation are an interesting and cheap source of medicinal and nutritional ingredients, especially when huge amount of byproducts are produced (sometimes 50% of the harvested material). In this context, development of healthcare products from fruit and vegetable residues could be a feasible approach for their value added utilization contributing to environmental clean-up at the same through their safe and efficient disposal. Present status and future prospect for lucrative application of food plant residues as sources of phytochemicals and nutraceutical compounds and their cleansing impact on environment are discussed in the paper
PUBLISHED
Keywords: Carbohydrates; Phytochemicals; Nutraceuticals